Does radiotherapy treatment alter the pulp condition in patients with head and neck cancer? A systematic review - Thalles Eduardo RIBEIRO; Veridiana Resende NOVAIS; Carlos ESTRELA; Maria Luiza Lima SANTANA; Giampiero ROSSI-FEDELE; Daniel de Almeida DECURCIO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The main purpose of this study was to answer the question: "Can radiotherapy cause changes in the dental pulp condition of patients treated with irradiation in the head and neck region?" Clinical observational studies in adults with head and neck cancer undergoing treatment with ionizing radiation, longitudinal or cross-sectional follow-up to measure oxygen saturation (SpO2), and/or pulp sensitivity test to cold stimulation, were considered eligible. A systematic literature search was performed in six different databases, including the gray literature, and in article references. Two independent evaluators selected the studies, extracted the data, recorded the data on electronic spreadsheets, and then evaluated the methodological quality using the Checklist for Quasi-Experimental Studies tool devised by JBI. The data were assessed qualitatively using the Synthesis Without Metanalysis (SWiM) guidelines. After removing the duplicate articles, carefully analyzing the titles and abstracts, and reading the papers in full, seven studies were included. Four of the studies evaluated applied the cold sensitivity test, two associated pulse oximetry and cold sensitivity, and only one used just pulse oximetry. Evaluation using the cold sensitivity test and pulse oximetry in the initial periods before radiotherapy showed a decrease in the sensitive response and in SpO2 levels during a maximum period of 1 year. However, analyses thereafter indicated a normal response in both tests from 5 to 6 years after the end of radiotherapy treatment. Radiotherapy causes changes in pulp behavior patterns in the short term; however, recovery and return to average values occurs after long periods.